014 Efficacy and safety of perampanel for myoclonic and absence seizures: studies 332, 311 and 232. Issue 6 (27th May 2022) - Brandt, Christian; Ben Renfroe, J; Ngo, Leock Y; Patten, Anna; Malhotra, Manoj
Abstract : Background: This post hoc analysis assessed the efficacy and safety of adjunctive perampanel in adult/adolescent/paediatric patients with myoclonic and absence seizures during Phase II/III clinical studies. Methods: During Study 332 (NCT01393743 ), patients aged ≥12 years with generalised tonic-clonic seizures (GTCS) received placebo/adjunctive perampanel 8-mg/day. In Study 311 (NCT02849626 ), patients aged 4–<12 years with focal-onset seizures/GTCS received perampanel ≤16-mg/day. In Study 232 (NCT01527006 ), patients aged 2–<12 years with epilepsy received perampanel ≤0.18-mg/kg/day. Data from patients with baseline myoclonic and/or absence seizures were pooled. Assessments included median percent change in seizure frequency/28 days and treatment-emergent adverse events (TEAEs). Results: Overall, 66/393 patients had myoclonic seizures (placebo, n=23; perampanel, n=43) and 72/393 had absence seizures (placebo, n=33; perampanel, n=39); patients with both seizure types are counted twice. Reductions in seizure frequency/28 days were observed with placebo and perampanel: myoclonic, 52.5% and 24.6%; absence, 7.6% and 25.1%, respectively. TEAEs with placebo and perampanel occurred in 18 (78.3%) and 36 (83.7%) patients with myoclonic seizures, and 25 (75.8%) and 34 (87.2%) patients with absence seizures, respectively; most common TEAEs with perampanel were dizziness and fatigue. Conclusion: These data suggest adjunctive perampanel does not worsen myoclonic/absence seizures in adult/adolescent/paediatric patients. Funding: Eisai Inc. stella_ngo@eisai.com 32